ANALISIS AKUNTANSI PERTANGGUNGJAWABAN DALAM PENILAIAN KINERJA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA SEMPULUR, KABUPATEN MAGELANG - Arif, Didik Muhamad; Imron, Moch (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2015)
The purpose of this study is to find the application of accounting accountability in performance evaluation of based on the regulation of health assessment cooperativesf. Aspects assessment health cooperatives that used in the capital are aspects, management aspects of, aspects growth and independence. The data used in research it will be reports on the results of members meetings annual from 2012 until the year of 2014.metoda used an author in this research is method descriptive. The research results show that the implementation of accounting accountability in performance evaluation of based on the regulation cooperatives and smes minister no.14 2009 on the capital 2012 categorized good criteria healthy weight value 35,91 34,28-42,85, 2013 categorized pretty good with criteria pretty healthy value 30,78bobot 25,71-34,28dan in 2014 categorized good criteria sehatnilai 34,28 34,28-42,85 weight.Performance evaluation of management aspects of in 2012 and last until 2014 categorized good criteria healthy weight value 34,98 34,28-42,85.While assessment performance aspects independence and growth in 2012 categorized not very nice criteria were very unhealthy value 6.24 0-8,57 weight.In 2013 and 2014 categorized less than good criteria unhealthy value 23,54 with weights 17,14-25,71.